Arsen'ev's Lament: A Century of Change to Wildlife and Wild Places in Primorye, Russia. Issue 3 (1st December 2020) - Slaght, Jonathan C.
Abstract: In 1900, Vladimir Arsen'ev arrived in a remote corner of the Russian Empire on the cusp of significant change. Forests in the Ussuri Kray (now Primorskiy Kray, or Primorye) were wild, wildlife was abundant, and the human population was low. Twenty-one years later, after witnessing a sustained influx of settlers and a reduction of wildlife, in his introduction to Across the Ussuri Kray [ Po Ussuriiskomy kraiu ], a travelogue about his experiences in the region, Arsen'ev mourned the passing of this unique time and place. This article outlines Arsen'ev's contributions to our understanding of Primorye's wildlife in the early twentieth century, describes what led to the reductions in wildlife he witnessed and offers a summary of how wildlife and wilderness look in the region today.